Legal Protection for Victims of Revenge Porn: Analysis From The Perspective of Criminal Law and Public Ethics - Heny Saida Flora; Lina Maulidana; Darsis Humah (PT. Hafasy Dwi Nawasena, 2026)
The development of digital technology has triggered an increase in cyber-based crimes, including the phenomenon of revenge porn, which has serious psychological, social, and legal impacts on victims. This study aims to analyze the effectiveness of legal protection for victims of revenge porn from the perspective of criminal law and public ethics, while also identifying normative weaknesses in Indonesian legislation. The research method used is normative legal research with a legislative and conceptual approach, through a literature review of primary, secondary, and tertiary legal materials analyzed qualitatively. The results show that legal protection for victims of revenge porn is still suboptimal due to unclear norms, disharmony between regulations, and the dominance of a moralistic approach that is not victim-oriented. Existing laws do not clearly differentiate between perpetrators and victims, potentially leading to criminalization of victims. Furthermore, legal implementation still faces obstacles in the form of inconsistent interpretations by officials and a strong culture of victim blaming in society. From a public ethics perspective, revenge porn is a violation of privacy and human dignity that requires a multidimensional response. Therefore, it is necessary to reformulate legal norms based on the principle of consent, harmonize regulations, and strengthen the victim-based justice approach in order to realize fair and comprehensive legal protection